Gunpowder and weaponry - Collier, James Lincoln, 1928- (Great inventions (Benchmark Books (Firm)), 2004)
Looks at how warfare was conducted before the invention of gunpowder, and discusses the effects of gunpowder on weapons and the ways of war.